Dampak Kualitas Sistem, Pengguna Sistem dan Organisasi dalam Pemanfaatan Kinerja Sistem Informasi Manajemen Rumah Sakit di RSU Dr. H. Koesnadi Bondowoso - Demiawan Rachmatta Putro Mudiono; Sri Hernawati; Saiful Bukhori (Multidisciplinary Journal, 2018)
Hospital Information Management System (HIMS) was part of a health information system that provided relevant information resources throughout the organization to supported effective decision made and hospital administration. This studied aims to analyzed the impact of system quality, system users, and organizations in the utilization of HIMS performanced. The type of researched used was the type of explanatory researched. The population in this studied amounted to 258 and 158 samples. Based on the tested results there was the influenced of system quality on system users with t statistics 3,219 (t statistics> t table 1.96). In addition there was no effected of system quality on the organization with t statistics 0.483 and there was no organizational influenced on the user system with t statistics 1.489. Furthermore there was the effected of system users on the utilization of SIMRS performanced with t statistics of 5.838 and there was an organizational influenced on the utilization of HIMS performanced with t statistics 3.589. The results were interrelated between variables so that to realized the utilization of HIMS performanced. Keywords: System quality, System Users, Organization, Utilization of Abstrak